A new species of the pollen-beetle genus Meligethes (Coleoptera: Nitidulidae) of the M. aeneus group from Greece, with review of the M. subaeneus complex - Audisio, Paolo; Mancini, Emiliano; de Biase, Alessio (Zootaxa, 2006)
A morphological analysis was performed, combined with field data on insect/host-plant associations to clarify the taxonomic scenario of the Palaearctic Meligethes subaeneus complex (Coleoptera, Nitidulidae, Meligethinae), including three European and Caucasian species (M. subaeneus, M. matronalis, M. epeirosi n.sp.) that are associated with flowers of Brassicaceae for larval development. The analysis was focused on the diagnosis and formal description of a new species, M. epeirosi n.sp. from NW Greece (Pindo Chain), which develops on Cardamine (s.str.) glauca Sprengel. The morphological variation of the true M. subaeneus in Europe was also analysed; the combined morphological and ecological evidence suggests that this species is structured in three main groups of European populations, which are probably the result of Pleistocene differentiation, suggesting an ongoing process of incipient speciation within this taxon.